Efficacy of the dental splints with antiseptic coat for mandibular fractures - Барило, Олександр Семенович; Кравчук, Павло Олександрович (ScienceRise: Medical Science, 2016)
Purpose of the study: the purpose of our study is an increase of efficiency of jaws fractures treatment by elaboration of the new method and new means of prevention of creation and adhesion of dental scurf on splinting dental constructions. Materials and methods. For improvement of hygienic state of oral cavity we offer the methodology of covering teeth and splints with enamel coat with antiseptic preparation. The base of enamel coat is Ftorlak, prepared according to classic recipes. For providing antiseptic effect and preventing adhesion of bacterial scurf on dental surface and splinting constructions we used Decamethoxin that was injected in ftorlak at the rate 25 mg of dry mass for 100 ml (0,025% solution). In our research we carried out the deep study and analysis of indices of oral cavity hygiene in patients with mandibular fractures, not depending of localization of the fracture line. Results. At study of the data of Fedorov-Volodkina index in the group of comparison was observed the significant worsening of hygiene index during the whole period of observation. Thus, at the beginning of study (first day) index was 1,18±0,10; as at 7 day – 2,50±0,24; as at 28 day – 3,99±0,18. At the same time in the main group at the beginning of research the difference with group of comparison was insignificant– 1,22±0,09 (р1>0,05) In further we observed the insignificant worsening of index, but it was reliably better than in the group of comparison: as at 7 day – 1,69±0,21 (р2<0,05); as at 28 day – 1,78±0,09 (р3<0,05). Analyzed the results of study of Green–Vermillion index (simplified index of the oral cavity hygiene), we had at the beginning of research (first day) the unreliable difference between the group of comparison (0,30±0,09) and main one (0,29±0,09) (р1>0,05). At 7 day we had the reliably better result between the group of comparison (1,26±0,17) and the main one (0,50±0,11) (р2<0,05). As at 28 day was observed the reliably better result between the group of comparison (2,29±0,22) and the main group (0,83±0,21) (р3<0,05) РНР (index of hygiene efficiency) at the beginning of research (first day) had unreliable difference between the group of comparison (0,29±0,09) and the main one (0,30±0,09) (р1>0,05). At 7 day we had the reliably better result between the group of comparison (1,59±0,21) and the main group (0,69±0,09) (р2<0,05). As at 28 day was observed the reliably better result between the group of comparison (2,04±0,22) and the main one (1,12±0,18) (р3<0,05). Gingivitis index (Silness-Loe) at the beginning of study had unreliable difference between the group of comparison (0,31±0,08) and the main one (0,31±0,11) (р1>0,05). At 7 day we had the reliably better result between the group of comparison (1,40±0,20) and the main group,69±0,08) (р2<0,05). As at 28day was observed the reliably better result between the group of comparison (2,39±0,19) and the main one (0,89±0,12) (р3<0,05). Studied the PMA index we had at the beginning of research (first day) unreliable difference between the group of comparison (9,96±0,95) and the main group (10,07±0,92) (р1>0,05). At 7 day we observed the reliably better result between the group of comparison (35,20±1,05) and the main one (2,06±0,91) (р2<0,05). As at 28 day we had the significant reliably better difference between the group of comparison (64,96±2,25) and the main one (31,15±0,95) (р3<0,05). Conclusion. Carried out the detailed analysis of the methods of observation, we created an algorithm of diagnostic of the oral cavity state and the state of dental tissues at mandibular fractures. Using this algorithm we carried out the study of patients, who underwent the treatment according to the standard scheme and application of splints with antibacterial coat. Antibacterial enamel coat favors the decrease of adhesion of microbial scurf and dental plaque at the treatment of mandibular fractures that prevents the development of inflammatory processes in parodentium